The Implementation of Merdeka Belajar Curriculum for the Seventh-Grade English Class - Septiana Purwani, Ratna; Budiraharjo, Markus (Universitas Negeri Semarang, 2024)
The Merdeka Belajar curriculum was established to promote Indonesia's educational goal and as part of attempts to restore learning. It is a more flexible curriculum framework that focuses on necessary information while also building students' character and competence. However, not all schools have implemented the Merdeka Belajar curriculum based on its principles. Therefore, this study aims to know the implementation of the Merdeka Belajar curriculum for seventh-grade English lessons in Gunungkidul. This study employed a qualitative method to get the data from three English teachers. The data was collected through semi-structured interviews and field observations. The results of the study revealed that the implementation of the Merdeka Belajar curriculum in grade seven junior high schools in Gunungkidul has not fully followed the Merdeka Belajar curriculum concept. Only one of the three teachers implemented the mandated curriculum according to the concept. Others demonstrated to have implemented several concepts, such as giving diagnostic tests to grade seven students, student-centered learning, teaching according to students' learning styles and abilities, and implementing formative and summative assessments following the concept of an independent curriculum. Nonetheless, the teachers enthusiastically support the adoption of the Merdeka Belajar curriculum for a variety of reasons, including material flexibility, applicability to real-world demands, and the development of creativity.